2011
DOI: 10.1002/cite.201000188
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Metal‐Organic Frameworks and Their Application in Asymmetric Catalysis and Stereoselective Separation

Abstract: The targeted synthesis of a desired stereomer plays a key role in life sciences, especially in the production of drugs. Up to date, this area is dominated by homogeneous chiral catalysts. Metal-Organic Frameworks (MOFs), a new class of porous materials, consisting of metal-oxo-clusters and multifunctional ligands could offer a platform for chiral heterogeneous catalysts combining the efficiency and in particular selectivity observed for homogeneous asymmetric catalysts with the advantages of heterogeneous cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
74
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(75 citation statements)
references
References 61 publications
1
74
0
Order By: Relevance
“…Interestingly, a similar cyclopropanation reaction with 1 R as the catalyst gave the desired products in less than 1 % yield and with modest ee values (Table 1, entry 4). The framework interpenetration in 1 R significantly reduced the open channel sizes, thus preventing the diffusion of the reagents into the Ru II /salen active sites in the interior of 1 R. The beneficial effect of a reducing agent for the cyclopropanation reaction was also observed for the homogeneous control reaction with the [Ru(L-Me 2 )(py) 2 ] catalyst: The cyclopropane products were obtained in a yield of 28 % and 53 % in the absence or presence, respectively, of NaBH(OMe) 3 (Table 1, entries 5 and 6). Finally, we have shown that 2 R is also an active catalyst for the cyclopropanation of both 1,3-pentadiene and ethyl vinyl ether, albeit in lower yields and with lower d.r.…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…Interestingly, a similar cyclopropanation reaction with 1 R as the catalyst gave the desired products in less than 1 % yield and with modest ee values (Table 1, entry 4). The framework interpenetration in 1 R significantly reduced the open channel sizes, thus preventing the diffusion of the reagents into the Ru II /salen active sites in the interior of 1 R. The beneficial effect of a reducing agent for the cyclopropanation reaction was also observed for the homogeneous control reaction with the [Ru(L-Me 2 )(py) 2 ] catalyst: The cyclopropane products were obtained in a yield of 28 % and 53 % in the absence or presence, respectively, of NaBH(OMe) 3 (Table 1, entries 5 and 6). Finally, we have shown that 2 R is also an active catalyst for the cyclopropanation of both 1,3-pentadiene and ethyl vinyl ether, albeit in lower yields and with lower d.r.…”
mentioning
confidence: 74%
“…[3,7] Motivated by excellent asymmetric catalytic activities exhibited by many homogeneous metal/salen complexes [where an archetypical chiral salen ligand is (R,R)-1,2-cyclohexanediamino-N,N'-bis(3-tert-butyl-salicylidene)], [8] MOFs containing metal/salen building blocks have attracted a great deal of recent interest.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Chiral ligands can be used for the generation of homochiral porous MOFs, or chirality can be induced from the arrangement of achiral ligands within the structure. [54][55][56][57] Among the chiral ligands available, [58][59][60][61][62][63][64] bio-ligands, such as natural occurring peptides, are structurally rich and versatile with numerous metal binding sites. However, robust and highly porous MOFs based on these ligands are scarce in the literature.…”
Section: Ligand Design In Mofsmentioning
confidence: 99%